Masked Uncontrolled Hypertension Is Not Attributable to Medication Nonadherence. Issue 3 (September 2019) - Siddiqui, Mohammed; Judd, Eric K.; Dudenbostel, Tanja; Zhang, Bin; Gupta, Pankaj; Tomaszewski, Maciej; Patel, Prashanth; Oparil, Suzanne; Calhoun, David A.
Abstract : Masked uncontrolled hypertension (MUCH) in treated hypertensive patients is defined as controlled automated office blood pressure (BP; <135/85 mm Hg) in-clinic but uncontrolled out-of-clinic BP by ambulatory BP monitoring (awake [daytime] readings ≥135/85 mm Hg or 24-hour readings ≥130/80 mm Hg). To determine whether MUCH is attributable to antihypertensive medication nonadherence. One hundred eighty-four enrolled patients were confirmed to have controlled office BP; of these, 167 patients were with adequate 24-hour ambulatory BP recordings. Of 167 patients, 86 were controlled by in-clinic BP assessment but had uncontrolled ambulatory awake BP, indicative of MUCH. The remaining 81 had controlled in-clinic and ambulatory awake BP, consistent with true controlled hypertension. After exclusion of 9 patients with missing 24-hour urine collections, antihypertensive medication adherence was determined based on the detection of urinary drugs or drug metabolites by high-performance liquid chromatography–tandem mass spectrometry. Of the 81 patients with MUCH, 69 (85.2%) were fully adherent and 12 (14.8%) were partially adherent (fewer medications detected than prescribed). Of the 77 patients with true controlled hypertension, 69 (89.6%) were fully adherent with prescribed antihypertensive medications and 8 (10.4%) were partially adherent. None of the patients in either group were fully nonadherent. There was no statistically significant difference in complete or partial adherence between the MUCH and true controlled groups ( P =0.403). Measurement of urinary drug and drug metabolite levels demonstrates a similarly high level of antihypertensive medication adherence in both MUCH and truly controlled hypertensive patients. These findings indicate that MUCH is not attributable to antihypertensive medication nonadherence.